Implementasi Teori Uses and Gratification pada Instagram Komunitas Parkour Jakarta untuk Memperkuat Kegiatan Promosi - Ilman, Faqih; Hadi, Sigit Pramono (Lembaga Yasin AlSys, 2024)
This article discusses the development of social media, especially Instagram, as a promotional platform for the Jakarta Parkour community. Social media makes it easy to build relationships and interact with other users. Instagram, with 22 million active users in Indonesia, is an effective choice for promotion, especially for the Jakarta Parkour community. The article also notes the development of Parkour in Indonesia and the establishment and development of the Jakarta Parkour Community through social media, especially Instagram. This scientific article discusses how Instagram social media can be effectively used in promoting the Parkour Jakarta community using the Uses and Gratifications theory and using the AISAS model to identify the promotional effects used by Pakour Jakarta on Instagram social media. This research aims to understand how Instagram social media fulfills these characteristics in the promotional effects used by the Jakarta Parkour community. The research approach used is qualitative. The results of this research are the Jakarta Parkour community's Instagram social media with reference to the Uses and Gratification theory which includes audience characteristics. This community has fulfilled various characteristics such as using Instagram to fill free time, escape from routine, create social bonds, provide entertainment, interact socially, provide information, provide relaxation, and create joy. The promotional effect of the Jakarta Parkour Community through Instagram social media using the AISAS model, shows that the use of this platform provides various benefits, including the ability to attract attention, create interest, facilitate information search, encourage action, and support information sharing. This research highlights that the use of social media Instagram effectively strengthens promotional interactions and participation in promoting a community.